The Effect of Current Ratio, Net Profit Margin, and Total Asset Turnover on Profit Growth at PT Indofood Cbp Sukses Makmur Tbk for the Period 2012-2021 - Amilah, ST Nor; Habibi, Azwar (Universitas Islam Negeri Sumatera Utara, 2023)
This study was conducted to determine several factors that affect earnings growth. Is a quantitative study using multiple linear regression analysis research methods. The data used is secondary data with a population of quarterly financial reports of PT Indofood cbp Sukses Makmur Tbk obtained a sample of 40 samples of financial statements. The results of this study indicate that: Current ratio has no significant effect on earnings growth with a value of (Thitung = 1.243 < Ttable = 2.021. As for profitability, the significance is greater than α (Sig. > α), namely 0.222> 0.05. Net profit margin has a significant positive effect on earnings growth, namely (Thitung = 2.309 < Ttabel = 2.021. For profitability, the significance is smaller than α (Sig. < α), namely 0.027 < 0.05. total asset turnover has a significant effect on profit growth with a value of (Thitung < Ttabel), namely 6.565 < 2.021. As for profitability, the significance value is smaller than α (Sig. < α), namely 0.000 < 0.05. Current ratio, net profit margin, and total asset turnover simultaneously affect profit growth with the results of the Fcount value of 16.305 significance of 0.001. The Ftable value is 2.839, a decision can be made to reject H0 which states that there is no influence between other variables. Accept Ha which states the influence between other variables because the Fcount value is greater than Ftable (16.305> 2.839), the profitability value of significance is smaller than the α value (Sig. < α), namely 0.001 < 0.05.